ANALISIS KADAR BESI (Fe) PADA BAYAM MERAH (Iresine herbstii hook) DAN BAYAM HIJAU ( Amaranthus tricolor sp ) YANG DIKONSUMSI MASYARAKAT - Nelma Nelma (Pascasarjana Universitas Negeri Medan, 2014)
Abstract Spinach (Spinacia oleracea) is the vegetable which has high nutrition content. It places spinach in King of vegetable’s range. Contains few calories but rich in vitamin A, vitamin C and iron mainly. Research comparison of the levels of iron in red and green spinach was done in chemical laboratory of polytechnic health Ministry of Health Indonesia Medan Analis Health department and Health Laboratory Medan on march-july 2013. This study aimed to know iron levels in red and green spinach. Study samples were 8 red spinach and 8 green spinach randomly chosen from Aksara market Medan. Iron levels were examined by atomic absorption spectrophotometer (λ =248,3 nm). Quantitative test result showed iron levels in green spinach (6,66 mg% - 8,18 mg%) was higher than red spinach (2,63 mg% - 4,34 mg%)Keywords: spinach, iron (Fe) level, atomic absorption spectrophotometer